Predictive value of the second‐trimester fibronectin concentration for severe preeclampsia: A prospective nested case–control study in China. Issue 7 (6th April 2022) - Li, Wei; Lin, Xiaowen; Chen, Yuchen; Liu, Kun; Yang, Weibin; Zeng, Sifan; Zhang, Jing
Abstract: Aim: To evaluate the value of the second‐trimester fibronectin concentration, alone and in combination with other markers (e.g., mean arterial pressure, inhibin A), in the identification of women who subsequently develop severe preeclampsia. Methods: For this prospective nested case–control study, serum from pregnant women (gestational age 15–22 weeks) who underwent routine Down syndrome screening was analyzed. The women were tracked to delivery and assigned to the severe preeclampsia or control group, according to whether they developed severe preeclampsia. Each woman who later developed severe preeclampsia was paired with five healthy women with pregnancies of similar gestational age (± 1 week). Fibronectin, inhibin A, human chorionic gonadotropin, placental growth factor, cysteine, and homocysteine concentrations were measured in 44 cases in the severe preeclampsia group and 220 cases in the control group. The body mass index and mean arterial pressure were calculated. All results were compared between the two groups. Logistic regression analysis and receiver operating characteristic curve construction were conducted for markers differing significantly between two groups. Results: The second‐trimester fibronectin value was positively correlated with severe preeclampsia and predicted 67.7% of severe preeclampsia cases. The combination of fibronectin, inhibin A, and mean arterial pressure predicted 76.7% of severe preeclampsia cases; predictive values for combinations of fibronectin with mean arterial pressure or inhibin A were 75.4% and 74.6%, respectively. Combination with these other markers increased the predictive value of fibronectin. In addition, fibronectin was more powerful for the late severe preeclampsia and severe preeclampsia without fetal growth restriction subgroups. Conclusions: The second‐trimester fibronectin concentration can be used to predict severe preeclampsia.